2012
DOI: 10.1161/circinterventions.112.972323
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Assessment of Ticagrelor Versus Prasugrel Antiplatelet Effects in Patients with ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Ticagrelor and prasugrel provide stronger platelet inhibition compared with clopidogrel. Direct pharmacodynamic comparison between them has not yet been reported in ST-segment-elevation myocardial infarction. Methods and Results-In a prospective, single-center, single-blind study, 55 out of 117 (47%) screened consecutive STsegment-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention were randomized to either ticagrelor 180 mg loading followed by 90 mg bid, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
232
1
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(263 citation statements)
references
References 38 publications
19
232
1
11
Order By: Relevance
“…Opiates also delay gastric emptying and therefore can delay the absorption and onset of action of oral P2Y 12 inhibitors, which rely on intestinal absorption [27][28][29][30]. Vomiting of stomach contents may lead to uncertainty about absorption of oral therapy and patients can also be unable to swallow e.g.…”
Section: Unmet Need In Antiplatelet Therapymentioning
confidence: 99%
“…Opiates also delay gastric emptying and therefore can delay the absorption and onset of action of oral P2Y 12 inhibitors, which rely on intestinal absorption [27][28][29][30]. Vomiting of stomach contents may lead to uncertainty about absorption of oral therapy and patients can also be unable to swallow e.g.…”
Section: Unmet Need In Antiplatelet Therapymentioning
confidence: 99%
“…Beside the higher baseline PR in STEMI patients, a limited or delayed intestinal absorption of orally administered drugs is another major contributor to this observation. (6)(7)(8) Previous pharmacokinetic studies have demonstrated that chewable aspirin and crushed clopidogrel administration increased the rate of drug absorption compared to integral tablets, when administered orally. (9,10) Recently, crushed ticagrelor tablets, administered orally or via a naso-gastric tube, has been shown to be feasible and resulted in increased plasma concentration of ticagrelor and its active metabolite at an earlier time point compared to integral tablets.…”
Section: Introductionmentioning
confidence: 99%
“…The early and strong platelet inhibition seems to be of paramount importance in patients with STEMI undergoing Percutaneous Coronary Intervention (PCI) [3]. Newer P2Y12 receptor inhibitors prasugrel and ticagrelor (newer P2Y12) exhibit more rapid, potent, and consistent platelet inhibition than clopidogrel and reduce the risk for ischemic cardiovascular complications [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Newer P2Y12 receptor inhibitors prasugrel and ticagrelor (newer P2Y12) exhibit more rapid, potent, and consistent platelet inhibition than clopidogrel and reduce the risk for ischemic cardiovascular complications [4][5][6][7][8][9][10]. In STEMI patients, an initial delay in the onset of newer P2Y12 antiplatelet action was observed and ticagrelor did not appear superior to prasugrel [3]. However, patients with Cardiogenic Shock (CS) or after Cardio Pulmonary Resuscitation (CPR) were mostly excluded from randomized studies and data on the clinical efficacy of these drugs comparing to clopidogrel in these patients is sparse [11][12][13].…”
mentioning
confidence: 99%